A Meta-Analysis of Dextrose Infusion as Perioperative Strategy on Preventing Postoperative Nausea and Vomiting - Nabiel Erisadana, Rifaldy; Pratama, Muhamad Rizal Hadi; Muhammad, Faliqul Bahar; Gemawan, Taufiq; Fatmarita, Lia; Ekawaty, Uli Artha; Danar Sumantri, Syahrul Mubarak (Majalah Anestesia & Critical Care, 2024)
Introduction: Dextrose infusion was introduced as a non-pharmacological perioperative strategy to decrease the PONV incidence. However, current published studies reported remain inconsistent and debatable results regarding the efficacy. This research was conducted to improve the evidence-based perioperative strategies of administering dextrose infusion to prevent PONV. Method: A literature search was conducted for randomized controlled trial studies (RCTs) in patients who administered dextrose infusion compared to other infusion fluid perioperatively. A quantitative analysis using Review Manager 5.4 was performed with a 95% confidence interval that was visualized in the forest plot graph using the fixed-effects or random-effects model based on the heterogeneity. Results: A total of 18 RCTs studies analyzed demonstrated there were significant differences in composite PONV (RR, 0.66, 95% CI 0.60, 0.74; P < 0.00001; I2=46%), patients with postoperative antiemetic rescue requirements (RR, 0.67, 95% CI 0.53, 0.86; P < 0.001; I2=68%), and postoperative blood glucose levels (SMD, 2.63, 95% CI 1.76, 3.50; P < 00001; I2=97%). However, there were insignificant results in PONV severity (SMD, -0.94, 95% CI -2.20, 0.31; P = 0.14; I2=97%), patients with analgesic requirements (RR, 0.84, 95% CI 0.60, 1.19; P = 0.33; I2=81%), dose of analgesic requirements (SMD, -2.31, 95% CI -5.76, 1.14; P = 0.19; I2=99%), and PACU stay (MD, -24.73, 95% CI -66.07, 16.61; P < 0.24; I2=99%). Conclusion: This meta-analysis demonstrated that administering dextrose infusion perioperatively prevents both the PONV incidence and postoperative rescue antiemetic requirements, and also increase postoperative blood glucose levels. However, dextrose infusion is not associated with reducing the PONV severity, postoperative analgesic requirements, a dose of postoperative analgesic use, and PACU stay. .